Medical Cannabis: Effects on Opioid and Benzodiazepine Requirements for Pain Control. Issue 11 (November 2019) - O'Connell, Megan; Sandgren, Megan; Frantzen, Leah; Bower, Erika; Erickson, Brian
Background: There is currently little evidence regarding the use of medical cannabis for the treatment of intractable pain. Literature published on the subject to date has yielded mixed results concerning the efficacy of medical cannabis and has been limited by study design and regulatory issues.Objective: The objective of this study was to determine if the use of medical cannabis affects the amount of opioids and benzodiazepines used by patients on a daily basis.Methods: This single-center, retrospective cohort study evaluated opioid and benzodiazepine doses over a 6-month time period for patients certified to use medical cannabis for intractable pain. All available daily milligram morphine equivalents (MMEs) and daily diazepam equivalents (DEs) were calculated at baseline and at 3 and 6 months.Results: A total of 77 patients were included in the final analysis. There was a statistically significant decrease in median MME from baseline to 3 months (−32.5 mg; P = 0.013) and 6 months (−39.1 mg; P = 0.001). Additionally, there was a non–statistically significant decrease in median DE at 3 months (−3.75 mg; P = 0.285) and no change in median DE from baseline to 6 months (−0 mg; P = 0.833).Conclusion and Relevance: Over the course of this 6-month retrospective study, patients using medical cannabis for intractable pain experienced a significant reduction in the number of MMEs available to use for pain control. No significant difference was noted in DE from baseline. Further prospective studies are warranted to confirm or deny the opioid-sparing effects of medical cannabis when used to treat intractable pain.